Heme Oxygenase (HO)-1 as an Immunoregulator in Health and Disease - Lianos, Elias; Detsika, Maria G. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Heme oxygenase (HO)-1 is a well-known, cytoprotective enzyme, responsible for the enzymatic conversion of heme into the anti-apoptotic and antioxidant by-products, biliverdin, bilirubin and carbon monoxide. However, HO-1 also regulates responses via mechanisms that are independent of the generation of heme degradation products. The current Special Issue contains research and review articles on the effect of heme oxygenase on immune-related cellular and physiological cascades and functions including effects on innate immunity, adaptive immunity, inflammation and complement activation. A description of the role of HO-1 in immune regulation directly or via its by-products is depicted on various forms of infection, viral and bacterial, immune-mediated injury such as renal injury, allergic airway inflammation, cancer and metabolism. Thus, the current Special Issue aims to serve as a detailed, analytical and up-to-date guide of the recent advances on the immunomodulatory properties of HO-1.